Tvorba 3D assetů do digitálních her - Mrkus, Matyáš (Vysoké učení technické v Brně. Fakulta výtvarných umění, 2025)
Diplomová práce se zaměřuje na proces tvorby plně funkčních 3D assetů do digitálních her. Rozebírá ideový směr řemeslnosti v konfliktu s autorstvím a snaží se poskytnout klíč k navigaci v soudobém průmyslovém ekosystému. Jejím výstupem jsou příkladové modely a zdokumentování celého procesu jejich tvorby, včetně chybných kroků, sloužící informačně pro budoucí využití. Cílem je přiblížit se uplatnitelnosti v herním průmyslu v oblasti 3D grafiky při přechodu ze školního prostředí.

The thesis focuses on the process of creating fully functional 3D assets for digital games. It analyzes the ideological direction of craftsmanship in conflict with authorship and attempts to provide a key to navigating the current industrial ecosystem. Its output consists of example models and documentation of the entire creation process, including mistakes, serving as a reference for future use. The goal is to approach applicability in the gaming industry in the field of 3D graphics when transitioning from the academic environment.
3D asset creation for digital games
Keywords: 3D assety; 3D grafika; digitální hry; herní průmysl; character art; 3D assets; 3D graphics; digital games; video game industry; character art